Heranca das reacoes do feijoeiro (Phaseolus vulgaris L.) ao virus do mosaico rugoso do feijao - Machado, P.F.R. (IICA, Turrialba (Costa Rica), 2014)
Tesis (Mag. Sc.) -- IICA, San José (Costa Rica), 1973